A Review of Registered Clinical Trials on Dietary (Poly)Phenols: Past Efforts and Possible Future Directions - Mirko Marino; Cristian Del Bo’; Daniela Martini; Marisa Porrini; Patrizia Riso (Foods, 2020)
In recent years, the increasing number of studies on polyphenol demonstrates the efforts in elucidating the potential role of these bioactives on human health. This study reviews the main topics and characteristics of clinical trials on polyphenols registered over the last 20 years, in order to track past and current efforts as well as to highlight the main research gaps in this field. The review was conducted by collecting trials registered in ClinicalTrials.gov and International Standard Randomised Controlled Trial Number (ISRCTN) registry. Overall, 750 clinical trials were selected and included in the final evaluation. Most of the trials were performed on extracts or pure compounds followed by studies conducted on polyphenol-rich foods, in particular berries. A total of 520 clinical trials focused on health effects, 55 on bioavailability, and 175 on both. Regarding outcomes, 139 registered intervention studies had the lipid profile and blood pressure as primary outcomes. The overview provided by this analysis also emphasizes the emerging interest in new outcomes related to polyphenols intervention such as microbiota composition and the evaluation of inter-individual variability in response to the intake of polyphenols. Our review underlines the need of further trials covering unexplored or debated research aspects and provides insights for the design and development of future intervention studies and related research areas.